Effects of mothers’ health beliefs on the dental status of schoolchildren in Taiwanese and immigrant women - Ying-Ying Lo; Pei-Liang Lee; Hsien-Wen Kuo (BMC Oral Health)
Abstract Backgrounds Limited evidence suggested that the Health Belief Model (HBM) had been used to explain how children were influenced by their mothers' health behaviors amid the rapid increase in international marriages in Taiwan. This study aimed to explore the health beliefs of immigrant and Taiwanese mothers regarding their children's dental caries status using the HBM. Methods This study employed a cross-sectional design. A total of 157 Taiwanese mothers, 29 mothers from China, and 64 mothers from Southeast Asia were purposively selected from 11 elementary schools. Each participant completed a structured questionnaire that included socio-demographic information, lifestyle habits, self-perceived oral health beliefs, and oral hygiene behaviors. Dental records of children aged 6–12 were obtained from local dentists at each school. Results Taiwanese mothers scored significantly higher in perceived susceptibility, perceived severity, and perceived benefit compared to mothers from China and Southeast Asia. However, there were no significant differences in the dental status of children among the three groups. A multiple linear regression model, adjusted for covariates, indicated that higher Health Belief scores in mothers were associated with lower dental caries in their children. Conclusion While environmental and genetic factors influenced dental caries in children, our findings demonstrated that a mother's health beliefs regarding oral hygiene significantly affected her children's dental status.